STRATEGI KOMUNIKASI PEMASARAN DALAM MEMPERTAHANKAN LOYALITAS PELANGGAN INDOMARET DI KOTA BATAM - Hati, Putri Dias Permata; Cindoswari, Ageng Rara (SCIENTIA JOURNAL, 2023)
Modern retail is a way for companies to retail their products to final consumers for personal needs. Batam City is one of the cities that has a permit to establish a modern retail business, one of which is Indomaret. This study found a problem, namely a decrease in the number of customers in the last 3 years at 3 Indomaret stores in Batam City. The purpose of this study is to describe forms of communication and promotion in maintaining Indomaret customer loyalty in Batam City. This research method uses a qualitative approach with data collection techniques through observation and interviews using purposive sampling method. The research analysis used the credibility test and the transferability test. The results of this study found several factors causing a decrease in the number of Indomaret customers in Batam City, including bad customer experience so that customers were disappointed such as unfriendly service, employees who were not focused and less creative in delivering promotions, product prices did not match the price tags displayed, long service or long queues, internal employee factors that affected sales declines such as not understanding the target market.